The Effect of a Restricted Feed Ration on Dairy Cow Response to Containment From Feed Using a Virtual Fence - Colusso, Patricia I.; Clark, Cameron E. F.; Green, Alexandra C.; Lomax, Sabrina (Frontiers in Animal Science, 2021)
Dairy cattle are offered various amounts of feed which they deplete through time. A reduction in the amount of feed allocated to cows may impact their containment using a virtual fence (VF). Pre-commercial neckbands (eShepherd®, Agersens, Melbourne, VIC) deliver an audio tone (AT) to the individual cow when it reaches the VF, and this is followed by an electrical pulse (EP) if they continue forward movement. No further stimuli are delivered if the cow stops or turns around. Thirty-four non-lactating dairy cows were used across three blocks in a controlled field experiment evaluating the impact of feed restriction on the exclusion of cows from a lucerne cube feed source using a VF. Within each block cows were pre-trained to the VF system for six-days on pasture before being fed either a 1) Restricted (R, 12 ± 0.3kg) or 2) Above maintenance (+M, 20kg) lucerne cube ration each day. The treatment groups were then tested for four 30min tests (T1- T4) in test paddocks of 100m x 20m. For testing, a VF was set at 30m from the paddock entry and 2kg per cow of lucerne cube feed was placed at 90m. Only R cows crossed the VF to access the feed, thereby receiving more AT and EP stimuli in T1 and T2 as compared to +M cows (P ≤ 0.03). However, there was no difference between treatments in T3 and T4 as cows learned the test routine and to remain within the VF in the paddock context. These results suggest that feed restriction may impact the exclusion of dairy cows from feed using a VF, but this effect is limited, and cows can learn to remain within a VF even when fed a restricted ration.